Estimation of the potential economic impacts of the oil and gas sector shutdown in Sergipe - Ribeiro, Luiz Carlos Santana (2024)
Despite promising prospects for the exploration of new oil and gas reserves in Sergipe, the Ministry of Mines and Energy announced in 2019 that Petrobras would close its headquarters in the state. In this context, this study estimates the economic impacts that the shutdown of the Oil and Gas sector would cause in Sergipe. We use a hypothetical extraction method in an interregional input-output model for Sergipe and the rest of Brazil. The main results indicate that the shutdown of this sector in Sergipe would lead to a total negative impact of R$ 4.7 billion in Brazil, with R$ 3.7 billion (79%) of the impact being in the state itself, while R$ 1 billion (21%) would spill over to the rest of Brazil. This would represent an 8.7% reduction in the gross production value of Sergipe. From a sectoral perspective, the sectors in Sergipe experiencing the greatest decline in activity, excluding the Oil and Gas extraction sector, would be Transportation, auxiliary activities, and postal services, Business services, Commerce, and Construction.